Nursing Students' Caring Behavior Towards Clinical Learning Readiness - Bhakti Permana; Ah. Yusuf; Henri Setiawan; Tri Antika Rizki Kusuma Putri (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: There was a high rate of psychological issues among students engaging in clinical practice. Students that focus on caring as their pedagogical foundation will be more equipped to provide nursing intervention in clinical situations. Objective: This research aimed to examine nursing students' caring behaviors as they relate to their readiness for clinical practice. Methods: A total of 122 nursing students from nursing schools in Bandung participated in this descriptive and cross-sectional study, with a response rate of 81.3%. Students' caring behavior and clinical readiness are assessed using the Casey-Fink Readiness for Practice Survey and the CBI-24 (Caring Behavior Instrument short form). Pearson correlation and linear regression tests in SPSS 26 were used to establish associations between the variables. Results: Findings demonstrated a statistically significant correlation between students' caring conduct and clinical preparation (sig 0.000; p0.05). The correlation between the two variables was 23.8% strong, which  was statistically significant. Student readiness for clinical practice was only strongly related to the connection factor. Nursing students' caring attitudes and clinical readiness were not significantly influenced by students' age, gender, or work situation. Conclusions: The level of empathy and social connection among nursing students influenced how well they were prepared for clinical practice. The development of students' caring behaviors, including self-assurance, competency, and respect, should be a primary goal of nursing education.